Weight loss, malnutrition, and cachexia in COVID‐19: facts and numbers. Issue 1 (31st December 2020) - Anker, Markus S.; Landmesser, Ulf; von Haehling, Stephan; Butler, Javed; Coats, Andrew J.S.; Anker, Stefan D.
Abstract: Patients with COVID‐19 disease are prone to develop significant weight loss and clinical cachexia. Three reports with altogether 589 patients that reported on weight loss and cachexia in COVID‐19 were identified. Disease severity of patients and the timing of the assessment during the disease course in these patients were variable—65 patients (11%) were intensive care treated at the time of assessment, and 183 (31%) were cared for in sub‐intensive or intermediate care structures. The frequency of weight loss ≥5% (that defines cachexia) was 37% (range 29–52%). Correlates of weight loss occurrence were reported to be raised C‐reactive protein levels, impaired renal function status, and longer duration of COVID‐19 disease. Underweight status by WHO criteria (BMI < 18.5 kg/m 2 ) was only observed in 4% of patients analysing data from seven studies with 6661 patients. Cachexia assessment in COVID‐19 needs assessment of weight loss. COVID‐19 associated cachexia is understood to affect muscle and fat tissue as is also seen in many other chronic illness‐associated forms of cachexia. There are many factors that can contribute to body wasting in COVID‐19, and they include loss of appetite and taste, fever and inflammation, immobilization, as well as general malnutrition, catabolic–anabolic imbalance, endocrine dysfunction, and organ‐specific complications of COVID‐19 disease such as cardiac and renal dysfunction. Treatment of COVID‐19 patients should include a focus on nutritional support and rehabilitative exercise whenever possible. Specific anti‐cachectic therapies for COVID‐19 do not exist, but constitute a high medical need to prevent long‐term disability due to acute COVID‐19 disease.